Architektura ośrodka pomocy społecznej w perspektywie kryzysów współczesnego świata - Rutkowski, Jarosław (Kultura-Społeczeństwo-Edukacja, 2023)
The article indicates that building an active social welfare center is a challenge in the face of the crises of the modern world. Therefore, building learners and conceptual social welfare centers is crucial for solving complex social problems of the modern world. In view of the panorama of burning crises outlined in the article, the need for subjective care for residents, especially those using the support of a social welfare center, was pointed out. It was emphasized that every citizen, regardless of their living condition, must be treated with appreciation. His participation and contribution to the reconstruction of our local and global world are important. Therefore, designing an open social welfare center that is dynamic to the challenges of the modern world requires a conceptual system defining the given architecture. It is determined by the interrelated components of organizational processes – ideological, programming, communication. Within the considered architecture, the network of relations binding the physical environment of the social welfare center is significant with human actions and experiences. This “between” as a combination of “in” and “among” expresses the spatial and temporal location of the actions taken. This perceived inter-space shapes shared experiences of caring for others. Then, within the imagination of the dialogue and the element of thinking, it is possible to design activities for the renewal of the modern world in a multidisciplinary and cross-sectoral way and to co-create optimal solutions to rebuild the life condition of people. This is reflected in tender actions embedded locally but intertwined globally. Building tender actions can be treated in the category of resistance, an active response to the life of residents in conditions of a specific order and formatted institutional practices. As a result, the recognized need to build and renew the world becomes a vitally important orientation for action. The aim of the article is a theoretical reflection on the architecture of a social welfare center in the perspective of crises of the contemporary world.